Estudo de minerais pesados, análise morfológica e datação U-Pb por ICPMS-LA de zircão detrítico : proveniência dos metasedimentos do Grupo Cuiabá, faixa Paraguai Norte-MT - Batalha, Raíza de Sousa (2016)
The Cuiabá Group (Internal Tectonic Zone of Paraguay Belt) was accumulated in the Neoproterozoic and is basically formed by a succession of sedimentary rocks initially deposited in continental environment, grading at the top to marine with glacial influence, intensely deformed and metamorphosed in low grade during the Brasilian-Pan-African Cycle). The study of the assembly of heavy minerals from metasedimentary rocks of the Cuiabá Group revealed that these are mainly ore opaque minerals, epidote, titanite, zircon, tourmaline, and rutile and to a lesser extent leucoxene, calcite and chlorite. The ZTR index and zircon content of these, increases toward the top of the stratigraphic column, indicating increased maturity of the base of the sediments (Campina de Pedra Formation) to the top (Coxipó Formation). With morphological analysis of detrital zircon, five families are discriminated: (F-1 and F-2) prismatic grains with preserved endings (F-3 and F-5) medium and long prisms rounded (F4) spherical grains. The relationship between families and zircon U-Pb ages is much dispersed, but euhedrals grains have significant occurrence in ± 1.4 Ga and are exclusive of Campina de Pedra Formation (base of the column), suggesting proximal sources. The U-Pb isotopic data through LA-ICPMS provide predominantly Mesoproterozoic ages indicating a main source from the west-northwest from the Sunsás Orogen. Paleoproterozoic grains are also present with maximum age recorded of 2.164Ma. According to the youngest zircon present, the maximum age for the deposition of the basin is Early Tonian (923 Ma). In the lower portion of the stratigraphic column the dominant ages are around 1.4 Ga, while in the intermediate part the main population of zircon has about 1.2 Ga. At the top of the column, there is a wide variation in the distribution of ages, but predominating grains of about 1.0 Ga. The joint analysis of heavy mineral studies, ZTR index, morphology and geochronological U-Pb data of detrital zircons, indicate a source for the Cuiabá Group from rocks of the western Amazon Craton. The pattern of results from bottom to top in the stratigraphy of the basin suggests variation in source areas and the maturity of sediments according to sedimentary environment that form the sedimentary basin. From these data, it is suggested that the deposition of the Cuiabá Group starts in a continental rift environment represented by Campina de Pedra Formation, going to a period of marine transgression with glacial influence generating Acorizal Formation, which evolved into a passive margin represented by the Coxipó Formation. The mark of the reversal of the sedimentary basin with glacio-isostatic adjustment occurs in the transition between Members Engenho and Pai Joaquim, which provides evidence of reworking of the oldest sources within the sedimentary basin.